Male infertility in Sertoli cell-only syndrome: An investigation of autosomal gene defects - GÜNEY, AHMET İLTER (WILEY, 2019)
Objectives To detect autosomal genetic defects and to determine candidate genes in Sertoli cell-only syndrome infertile men. Methods Single-nucleotide polymorphism + comparative genomic hybridization microarray technology was carried out on 39 Sertoli cell-only syndrome infertile patients in the present study. Array comparative genomic hybridization compares the patient's genome against a reference genome, and identifies uncover deletions, amplifications and loss of heterozygosity. Results A link between defective spermatogenesis genes and infertility was examined, and amplifications and deletions in several genes were detected, including homeobox gene; synaptonemal complex element protein 1; collagen, type I, alpha 1; imprinted maternally expressed transcript; and potassium voltage-gated channel subfamily Q member 1. Conclusions The present data suggest that several genes can play an important role in spermatogenesis and progression of Sertoli cell-only syndrome.
Keywords: array comparative genomic hybridization; infertility; Sertoli cell-only syndrome; DNA METHYLATION; EXPRESSION; PATTERNS; MEIOSIS